URIDINE PROMOTES NEURITE OUTGROWTH IN NEUROBLASTOMA CELLS - Jacquelyn Spathies; Gordon C. Tucker; Britto P. Nathan (Journal of Animal and Plant Sciences, 2024)
Neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s disease are the main causes of age-related dementia. These diseases can be due to neuronal cell death and/or impairment of neuronal growth and connections. Giant oyster mushroom (GOM), Pleurotus giganteus, is used as a nootropic to improve cognitive function. GOM can also be used to prevent the onset of dementia. The underlying mechanism behind the medicinal property of GOM is unclear. Previous studies have shown that GOM has a high concentration of uridine. In this study, we examined the effects of uridine on neurite outgrowth in the Neuro-2a (N2a) neuroblastoma cell line. We also examined the effects of various concentrations of uridine on neurite outgrowth in N2a cells. When exposed to uridine, N2a cells produced significantly longer neurite extensions (p≤0.001) and exhibited a significant increase in neurite-bearing cells (p≤0.001). The peak neurite promoting effect of uridine was at 100 𝜇M. Our results suggest uridine promotes neurite outgrowth in N2a cells (p≤0.001). Future studies are required to identify the mechanism(s) behind therapeutic potential of uridine on neurodegenerative diseases.
Keywords: Uridine; giant oyster mushroom; Pleurotus giganteus; neurite outgrowth; herbal medicine; Neuro2a; nerve regeneration; Alzheimer’s disease; Parkinson’s disease